2017
DOI: 10.1016/j.ijrobp.2017.06.2455
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Radiation Dose-Volume Liver Response in Biomechanical Deformable Image Registration

Abstract: Purpose Understanding anatomical and functional changes in the liver resulting from radiotherapy is fundamental to the improvement of normal tissue complication models needed to advance personalized medicine. The ability to link pre-treatment and post-treatment imaging is often compromised by significant dose-dependent volumetric changes within the liver that are currently not accounted for in deformable image registration (DIR) techniques. This study investigates using delivered dose, in combination with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…Three of the four TPSs (other than RayStation) have limited scope in altering registration parameters, but even different parameterizations of an algorithm (ANACONDA) failed to improve the performance significantly. While more recent state‐of‐the‐art DIR algorithms such as GIFTed Demons, and DIS‐CO, and advanced boundary conditions in biomechanical models may be able to provide some improvements, the full integration of new algorithms into existing TPSs is a lengthy process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three of the four TPSs (other than RayStation) have limited scope in altering registration parameters, but even different parameterizations of an algorithm (ANACONDA) failed to improve the performance significantly. While more recent state‐of‐the‐art DIR algorithms such as GIFTed Demons, and DIS‐CO, and advanced boundary conditions in biomechanical models may be able to provide some improvements, the full integration of new algorithms into existing TPSs is a lengthy process.…”
Section: Discussionmentioning
confidence: 99%
“…Simple rigid registration does not achieve a sufficient level of accuracy when volumetric changes and large patient motion occurs. 8 Studies have demonstrated the large volumetric response of the liver six weeks postradiation therapy, including hypertrophy and fibrosis. 9,10 One of the first studies to compare deformable image registration (DIR) techniques for pre-and post-RT liver cancer was conducted by Fukumitsu et al 11 The study compared commercially available DIR techniques in two treatment planning systems (TPS), MIM Maestro (MIM Software Inc., Cleveland, OH, USA) and Velocity (Velocity Medical Solutions, Atlanta, GA, USA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, specific tools, developed in academic institutions, are imported to commercial RT TPS [12,139,141]. Therefore, DIR algorithms require further development to better meet clinical needs, such as accounting for the different imaging modalities between planning and treatment delivery [133,142], near-real-time algorithms with graphic processing unit-based frameworks [139,[143][144][145], and anatomical properties simulated by finite element models [146][147][148][149][150].…”
Section: Uncertainties and Perspectives Of Dir In Rtmentioning
confidence: 99%
“…Recently, an expansion of Morfeus to model the volumetric response to the dose of the liver tissues was proposed. 9 The accuracy of the method to register CT scans pre-and post-RT of liver cancer was quantified for 7 patients by measuring the TRE of vessel bifurcation points. Modeling the dose response by adding dose boundary conditions in the biomechanic model allowed to significantly improve the DIR accuracy in comparison to using the standard model based on boundary conditions only on the liver surface.…”
Section: Introductionmentioning
confidence: 99%